HUBUNGAN PARTUS LAMA DENGAN KEJADIAN ATONIA UTERI PADA IBU BERSALIN DI BPM NY"S" DESA PRAMBON NGANJUK - Masyayih, Warda Anil; Hidayati, Nurul; Astuti, Arlia Shanti (PRIMA WIYATA HEALTH, 2024)
Prolonged labor is one of the risk factors that can cause uterine atony in mothers giving birth. Uterine atony is a condition where the uterine muscles do not contract properly after delivery, which can cause excessive bleeding. The aim of this research was to determine the relationship between prolonged labor and the incidence of uterine atony in mothers giving birth at BPM Ny "S" Prambon Village, Nganjuk. The research method used was analytical observational with a cross-sectional approach. The sample in this study was all mothers giving birth at BPM Ny "S" Prambon Village, Nganjuk in the period January-December 2022, totaling 120 people. The results showed that there was a significant relationship between prolonged labor and the incidence of uterine atony (p-value = 0.001). Mothers who gave birth with prolonged labor had a 3.8 times higher risk of experiencing uterine atony compared to mothers who gave birth with normal labor. Therefore, prevention efforts and appropriate treatment of prolonged labor are needed to reduce the incidence of uterine atony in mothers giving birth.